Temporal phenotyping of neutrophils in post-cardiac arrest syndrome and extracorporeal membrane oxygenation-assisted resuscitation: A pilot study - Yuki Chiba; Asumi Mizugaki; Takumi Tsuchida; Katsuhide Kayano; Kazuma Yamakawa; Takeshi Wada (PLoS ONE, 2025)
The role of extracorporeal membrane oxygenation in the immune response during cardiac arrest, as well as the role of the innate immune system—particularly neutrophils—in the pathophysiology of post-cardiac arrest syndrome, remains underexplored. This study aimed to comprehensively analyze the immune response in the pathology of post-cardiac arrest syndrome. This study included eight patients who experienced cardiogenic cardiopulmonary arrest and were treated for at least 1 week. Blood samples were collected immediately after the return of spontaneous circulation (day 0), as well as on days 1, 3, and 7. These patients formed the post-cardiac arrest syndrome group, and blood samples from five healthy volunteers served as controls. Neutrophil function over time was analyzed using CyTOF ® mass cytometry. Furthermore, patients in the post-cardiac arrest syndrome group were divided into extracorporeal membrane oxygenation and non-extracorporeal membrane oxygenation groups according to whether they received extracorporeal membrane oxygenation during resuscitation. Cytokine levels were compared between the two groups using LUMINEX ® . Three patients with post-cardiac arrest syndrome underwent extracorporeal membrane oxygenation. Compared with the control group, the post-cardiac arrest syndrome group showed fewer CD177-negative neutrophils and fewer strongly leukotriene B4 receptor 1-positive neutrophils. The extracorporeal membrane oxygenation group had more CD177-negative neutrophils and fewer CD16-seropositive neutrophils than the non-extracorporeal membrane oxygenation group. Differences in serum cytokine levels between the extracorporeal membrane oxygenation and non-extracorporeal membrane oxygenation groups were noted, with certain cytokines, including interleukin-6 and interleukin-8, decreasing over time only in the extracorporeal membrane oxygenation group. As the first in-depth immunological investigation of post-cardiac arrest syndrome, including neutrophil phenotyping, this study may inform clinical practices related to patient management and treatment strategies following cardiac arrest.